2020
DOI: 10.1186/s40813-020-00163-1
|View full text |Cite
|
Sign up to set email alerts
|

Farm data analysis for lifetime performance components of sows and their predictors in breeding herds

Abstract: Our objectives in this review are 1) to define the four components of sow lifetime performance, 2) to organize the four components and other key measures in a lifetime performance tree, and 3) to compile information about sow and herd-level predictors for sow lifetime performance that can help producers or veterinarians improve their decision making. First, we defined the four components of sow lifetime performance: lifetime efficiency, sow longevity, fertility and prolificacy. We propose that lifetime efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 83 publications
1
17
0
1
Order By: Relevance
“…The reasons for this could be that large herds have more advanced facilities than small-tomid herds, such as well-designed farrowing crates and milk replacer feeders [12,21]. Also, large herds are likely to have more human resources and a high level of genetic improvement than small-to-mid herds [15]. In addition, our results indicate that PWM is not likely to increase to 20% or higher even if PBA increases to 15 or more pigs, regardless of herd group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for this could be that large herds have more advanced facilities than small-tomid herds, such as well-designed farrowing crates and milk replacer feeders [12,21]. Also, large herds are likely to have more human resources and a high level of genetic improvement than small-to-mid herds [15]. In addition, our results indicate that PWM is not likely to increase to 20% or higher even if PBA increases to 15 or more pigs, regardless of herd group.…”
Section: Discussionmentioning
confidence: 99%
“…Also, another study reported that that large herd size was associated with decreased sow longevity [14]. Therefore, it is possible that herd-level factors could affect PWM because large herds have more advanced facilities, more human resources and a higher level of genetic improvement than small herds [12,15].…”
Section: Introductionmentioning
confidence: 99%
“…The typical way of monitoring piglet deaths during lactation has been to record them as herd-level preweaning piglet mortality, which is calculated by the recording systems [ 4 ]. However, if piglet deaths are recorded as herd-level information, it is not possible to perform multivariable analyses to examine multiple factors and their interactions in the same model [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reproductive performance of pigs depends on many factors. Due to its importance for swine production, it has been extensively analyzed for many breeds and situations [ 4 , 5 , 6 , 7 , 8 ]. Parity is a relevant factor, with the number of farrowings influencing sows’ fertility [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of parity is complicated by the influence of management and breeding systems [ 8 ], and whereas gilts can show a good prolificacy, their performance can vary greatly depending on the breed and management [ 16 ]. Similarly, older sows, with many farrowings, are more prone to reduced reproductive performance.…”
Section: Introductionmentioning
confidence: 99%